ハッコウウンホウ ニヨル カゼ ノ カンソク - 中村, 純二; ナカムラ, ジュンジ; NAKAMURA, Junji (国立極地研究所, 1975)
P(論文) Observation of the upper atmospheric wind velocity, diffusion constant and electric field by the method of artificial luminescent clouds has been carried out at Kagoshima Space Center for the past several years. From the viewpoint of the upper atmospheric dynamics, it is considered important that measurements of neutral wind velocities at the altitudes between 120 km and 200km and also of electric fields at the altitudes of about 200km are perfomed in the auroral zone, especially at Antarctica. In this article the writer suggests the following rocket experiments at Syowa Station: at the first stage, artificial sodium, barium and strontium cloud experiments in the evening using S-210 or S-310 rockets, and at the second stage, trimethyl-alminum cloud experiment at night time and also sodium cloud experiment with Zeeman photometers at day time. departmental bulletin paper